Click On Democracy : The Internet's Power to Change Political Apathy into Civic Action - DAVIS, Stave (Westview Press, 2002)
Click on Democracy examines the first national election in which the Internet played a major role. The contributors argue that the Internet's most profound political impact on Election 2000 has largely been missed or underestimated. The reason: the difference it made was more social than electoral, more about building political communities than about generating votes and money.Voter turnout has dwindled over the past forty years, and fewer Americans are involved in civic activities. The real story of the Internet is its emergence as a community builder - under the radar of most political observers who focus on large institutions - in a society that has become politically disengaged and disenchanted. The contributors to Click on Democracy talk at length with the people who are using the Internet in new and effective ways, and who are capitalizing on the Internet's power as a networking tool for civic action. Viewed from this bottom-up perspective, the Internet emerges as an exciting and powerful source of renewal for civic engagement.